Attitudes of the Adolescent Learning Disabled Students Related to School Relationships, Teacher Relationships, Family Relationships and Learning - Myers, L. Kay Hartwell; Wiseman, Douglas E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
Examined were the self-concept and attitudes of 88 learning disabled (LD adolescents related to school, teacher, family relationships, and specific learning disabilities. Ss were administered a 59-item questionnaire. Among findings were that LD students indicated positive experiences and attitudes of peers, regular and special classroom teachers, and family; and LD students did not perceive many of the negative social relationships discussed in the literature or the negative personal, behavioral, and learning characteristics attributed to them by the few studies in this area. (SBH)
ERIC Note: Paper presented at the Annual International Convention, The Council for Exceptional Children (56th, Kansas City, Missouri, May 2-5, 1978, Session T47).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Exceptional Child Research; Learning Disabilities; Parent Child Relationship; Peer Relationship; Secondary Education; Self Concept; Student Attitudes; Student Teacher Relationship; Speeches/Meeting Papers